Analisis Pengaruh Peran Kelompok Tani Dalam Peningkatan Produksi Padi di Kampung Sumber Mulya Distrik Kurik Kabupaten Merauke - Kwanimba, Herlin Rosanti; Widyantari, Ineke Nursih; Suriani, Wa Ode (MuJAgri: Musamus Journal of Agribusiness, 2024)
This research aims to analyze the variables that have an influence on increasing rice production in Sumber Mulya Village, Kurik District, and Merauke Regency. The research was conducted in January–February 2024. Quantitative descriptive methodology is the fundamental approach taken in this research. The deliberate selection was carried out in selecting the research location, namely in Sumber Mulya village, where the study was conducted. The purposive sampling technique was used in the sampling. Seventy-four respondents were used as the research sample size. Primary and secondary data were collected by interview, observation, and questionnaire. Multilinear regression analysis is the method used. The data is processed using SPSS 25. The results of this research show that the variables production vehicle, information vehicle, collaboration vehicle, and learning vehicle have a significant effect on increasing rice production with a significance level of 0.05. The learning vehicle variable is the dominant variable and has a positive influence with a regression coefficient value of 0.420 and a significance value of 0.000.